Dekonstrukcije nasprotja med reprezentacijo in prezentacijo od neoavantgarde do pomilenija - Toporišič, Tomaž (Amfiteater (Ljubljana), 2023)
The essay focuses on selected examples of the deconstruction of the opposition between representation and presentation, characteristic of post-mimetic art from the neo-avant- garde to the post-millennium. It discusses the authors who have been deconstructing the concept of drama and inventing new forms of redramatisation and post-dramatic intermediality from the 1960s to the present day. Despite persistently creating disrup- tions in the fictional textual cosmos, particular authors – such as Peter Handke in Offend- ing the Audience, the group Pupilija Ferkeverk in Pupilija, Papa Pupilo and the Pupilceks, Dušan Jovanović in Monument G and Play a Tumour in the Head and Air Pollution, Milan Jesih in Limits and The Bitter Fruits of Justice, Matjaž Zupančič in The Corridor and other plays, Dragan Živadinov and his team in Supremat and other farewell rituals, Oliver Frljić in Damned be the Traitor of His Homeland, Simona Semenić in 1981, and Žiga Divjak and Katarina Morano in various projects – establish a strong process of redramatisation in their theatrical texts and performances. It is as if, alongside the deconstruction of drama, they inject dramatic and theatrical elements into the post-dramatic process of staging and writing. Thus, post-mimetic art coexists with pre-mimetic art, as this “stripping down” of the representativity of drama led to the establishment of fiction.
Keywords: contemporary Slovenian drama; contemporary Slovenian theatre; Dušan Jovanović; Matjaž Zupančič; Milan Jesih; post-mimetic art; postmimetična umetnost; redramatisation; redramatizacija; sodobna slovenska drama; sodobno slovensko gledališče